The Labor of Play: the Political Economy of Computer Game Culture - (:unkn) unknown (My University, 2018)
This dissertation questions the relationship between computer game culture and ideologies of neoliberalism and financialization. It questions the role computer games play in cultivating neoliberal practices and how the industry develops games and systems making play and work indistinguishable activities. Chapter 1 examines how computer game inculcate players into neoliberal practice through play. In chapter 2, the project shows Blizzard Entertainment systematically redevelops their games to encourage perpetual play aimed at increasing the consumption of digital commodities and currencies. Chapter 3 considers the role of esports, or professional competitive computer game play, to disperse neoliberal ideologies amongst nonprofessional players. Chapter 4 examines the streaming platform Twitch and the transformation of computer gameplay into a consumable commodity. This chapter examines Twitch’s systems designed at making production and consumption inseparable practices. The dissertation concludes by examining the economic, conceptual, and theoretical collapses threatening game culture and the field of game studies.
Keywords: Computer Games; Marxism; Play; Work